1982
DOI: 10.1139/v82-132
|View full text |Cite
|
Sign up to set email alerts
|

Clathrate and other solid phases in the tetrahydrofuran–water system: thermal conductivity and heat capacity under pressure

Abstract: RUSSELL G. Ross and PER ANDERSSON. Can. J. Chem. 60,881 (1982). Solid phases in the tetrahydrofuran-water (THF-H20) system were investigated in the temperature range 100-260K and at pressures up to 1.5 GPa. Thermal conductivity, h, and heat capacity per unit volume, pc,, were measured, using the transient hot-wire method. We made measurements on solid phases having nominal compositions THF.17H20, THF,7.1H20, and THF.4.6H20, which we refer to as phases a , P, and y , respectively. Phase a is known to be a struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
58
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(64 citation statements)
references
References 14 publications
5
58
1
Order By: Relevance
“…This negative temperature dependence might result from methane gas in unconnected, intergranular porosity persisting after compaction. These results are consistent with published results except that Ross et al (1982) found a positive dependence on temperature on tetrahydrofuran (THF) hydrate. In a later development, Freifeld et al (2002) have tried to estimate thermal conductivity of hydrate/sand system using CT scan and their results were consistent with those of Waite et al (2002).…”
Section: Thermal Conductivitysupporting
confidence: 93%
“…This negative temperature dependence might result from methane gas in unconnected, intergranular porosity persisting after compaction. These results are consistent with published results except that Ross et al (1982) found a positive dependence on temperature on tetrahydrofuran (THF) hydrate. In a later development, Freifeld et al (2002) have tried to estimate thermal conductivity of hydrate/sand system using CT scan and their results were consistent with those of Waite et al (2002).…”
Section: Thermal Conductivitysupporting
confidence: 93%
“…There are limited data on the conductivity of clathrates at low temperatures. Their thermal conductivity has been measured on gas hydrates of structure I as CH 4 (Krivchikov et al 2005a), Xe (Handa & Cook 1987;Krivchikov et al 2006) and ethylene oxide (Cook & Laubitz 1983), and gas hydrates of structure II as tetrahydrofuran (Ross & Andersson 1982;Tse & White 1988;Andersson & Suga 1996;Krivchikov et al 2005b), dioxolane (Andersson & Ross 1983;Ahmad & Phillips 1987) and cyclobutanone (Andersson & Ross 1983) in a wide range of temperatures. It is very challenging to measure the bulk thermal conductivity of a homogeneous continuous solid (Krivchikov et al 2007).…”
Section: Thermal Conductivity Of Clathratesmentioning
confidence: 99%
“…They found the influence is a complex interplay among particle size, effective stress, porosity, and fluid-versus-hydrate filled pore spaces, not only porosity. With respect to temperature effect, many studies found that hydrates exhibit a glass-like temperature dependence of thermal conductivity (Andersson and Ross, 1983;Handa and Cook, 1987;Krivchikov et al, 2005Krivchikov et al, , 2006Ross et al, 1981;Ross and Andersson, 1982;Tse and White, 1988). Among these studies, the works of Krivchikov et al (2005Krivchikov et al ( , 2006 are interesting as they found that both methane and xenon hydrates show crystal-like temperature dependence below 90 K, while exhibiting glass-like behavior above 90 K. The effect of pressure has also been investigated by many groups (Andersson and Ross, 1983;Rosenbaum et al, 2007;Waite et al, 2007).…”
Section: Thermal Conductivity Of Gas Hydratementioning
confidence: 99%